Ordering of lateral nonuniformity of TiBx film and transition layer in the TiBx-GaAs system - Konakova, R.V.; Milenin, V.V.; Voitsikhovskyi, D.I.; Kamalov, A.B.; Kolyadina, E.Yu.; Lytvyn, P.M.; Lytvyn, O.S.; Matveeva, L.A.; Prokopenko, I.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
For TiBx film ~50 nm thick formed by magnetron sputtering from a pressed target onto the <100> GaAs substrate we experimentally revealed lateral nonuniformity ordering at microwave irradiation (frequency of 2.45 GHz, illuminance of 1.5 W/cm²). This correlates with improvement of the TiBx-n-n⁺-GaAs diode structure parameters after similar microwave treatment.